The best of the 2005 teaching & learning conference student achievement : the broader picture - Association for Supervision and Curriculum Development (Alexandria, VA : ASCD, 2006)
Collections of conference conducted by ASCD on teaching and learning and provides a broader pictures on student achievement
jilid 1. Preparing today's youth for tomorrow's world / James Comer (47 min.) -- jilid 2. Leadership for creating and sustaining high-performing secondary schools / Vera Blake (107 min.) -- jilid 3. Using multiple assessments to gather evidence of student learning / W. James Popham (81 min.) -- jilid 4. Assessment strategies that teach and increase achievement / Spence Rogers (100 min.) -- jilid 5. Reading and writing in the content areas / Sue Beers (98 min.) -- jilid 6. Myths and realities: what differentiation is and is not / Carol Ann Tomlinson (103 min.) -- jilid 7. Building background knowledge through vocabulary development / Robert J. Marzano (90 min.) -- jilid 8. Less teaching, more assessing learning via feedback / Grant Wiggins (89 min.) --
Title from container
Presenter: James Comer, Vera Blake, W. James Popham, Spence Rogers, Sue Beers, Carol Ann Tomlinson, Robert J. Marzano, Grant Wiggins
Keywords: Teaching and learning; Teaching; Educational tests and measurements